Microtubule-dependent Recruitment of Staufen-Green Fluorescent Protein into Large RNA-containing Granules and Subsequent Dendritic Transport in Living Hippocampal Neurons - Köhrmann, Martin (The American Society for Cell Biology, 1999)
Dendritic mRNA transport and local translation at individual potentiated synapses may represent an elegant way to form synaptic memory. Recently, we characterized Staufen, a double-stranded RNA-binding protein, in rat hippocampal neurons and showed its presence in large RNA-containing granules, which colocalize with microtubules in dendrites. In this paper, we transiently transfect hippocampal neurons with human Staufen-green fluorescent protein (GFP) and find fluorescent granules in the somatodendritic domain of these cells. Human Stau-GFP granules show the same cellular distribution and size and also contain RNA, as already shown for the endogenous Stau particles. In time-lapse videomicroscopy, we show the bidirectional movement of these Staufen-GFP–labeled granules from the cell body into dendrites and vice versa. The average speed of these particles was 6.4 μm/min with a maximum velocity of 24.3 μm/min. Moreover, we demonstrate that the observed assembly into granules and their subsequent dendritic movement is microtubule dependent. Taken together, we have characterized a novel, nonvesicular, microtubule-dependent transport pathway involving RNA-containing granules with Staufen as a core component. This is the first demonstration in living neurons of movement of an essential protein constituent of the mRNA transport machinery.